2023
DOI: 10.1371/journal.pone.0281587
|View full text |Cite
|
Sign up to set email alerts
|

Legionella longbeachae effector protein RavZ inhibits autophagy and regulates phagosome ubiquitination during infection

Abstract: Legionella organisms are ubiquitous environmental bacteria that are responsible for human Legionnaires’ disease, a fatal form of severe pneumonia. These bacteria replicate intracellularly in a wide spectrum of host cells within a distinct compartment termed the Legionella-containing vacuole (LCV). Effector proteins translocated by the Dot/Icm apparatus extensively modulate host cellular functions to aid in the biogenesis of the LCV and intracellular proliferation. RavZ is an L. pneumophila effector that functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…RavZ binds LC3 via an N‐terminal LC3‐interacting region (LIR) motif, which facilitates extraction of LC3 from the membrane and removal of the PE moiety (Yang et al , 2017a). Recent studies have also implicated RavZ in clearing ubiquitin from the bacteria‐containing vacuole (Kubori et al , 2017; Shi et al , 2023b), although direct DUB activity remains to be shown. The strategy RavZ uses to simultaneously remove and inactivate LC3 is akin to how the foot‐and‐mouth disease viral protease Lb pro cleaves ISG15 (Swatek et al , 2018), but whether this strategy has been adopted by other pathogen‐encoded Ub/Ub‐like proteases is an open question.…”
Section: Ub‐like Hydrolysis By Ce‐clan Proteasesmentioning
confidence: 99%
“…RavZ binds LC3 via an N‐terminal LC3‐interacting region (LIR) motif, which facilitates extraction of LC3 from the membrane and removal of the PE moiety (Yang et al , 2017a). Recent studies have also implicated RavZ in clearing ubiquitin from the bacteria‐containing vacuole (Kubori et al , 2017; Shi et al , 2023b), although direct DUB activity remains to be shown. The strategy RavZ uses to simultaneously remove and inactivate LC3 is akin to how the foot‐and‐mouth disease viral protease Lb pro cleaves ISG15 (Swatek et al , 2018), but whether this strategy has been adopted by other pathogen‐encoded Ub/Ub‐like proteases is an open question.…”
Section: Ub‐like Hydrolysis By Ce‐clan Proteasesmentioning
confidence: 99%
“…The effector RavZ was identified as a functional and important DUB in various Legionella species and was one of the first examples of bacterial effector proteins that manipulate host autophagy (30)(31)(32). RavZ harbors cysteine protease activity and hydrolyzes lipidconjugated LC3, a Ub-like protein incorporated in autophagic processes on autophagosome membranes (58).…”
Section: Protection From Degradation and Apoptosismentioning
confidence: 99%
“…This hydrolysis reduces the interaction of LC3 with other autophagosome proteins, thereby downregulating autophagy (30). Moreover, further studies revealed the interference of Ub recruitment to the replication vacuoles during Legionella infection upon RavZ activity (31,32). This raises the question of whether RavZ harbors DUB-like activity of RavZ in addition to its general cysteine protease activity towards lipid-conjugated substrates.…”
Section: Protection From Degradation and Apoptosismentioning
confidence: 99%